Capturing and disseminate local content in the cottage industry: perspective of master craftsman of weaving “mengkuang” leave / Norhayati Hussin ... [et al.] - Hussin, Norhayati; Mohd Tokiran, Nurul Syfa’; Shahibi, Mohd Sazili; Ahmad, Masitah (Faculty of Information Management, 2023)
This paper addresses the significant role of master craftsmen in capturing and disseminating local content towards sustaining the handicraft industry in Malaysia. Master craftsmen capture the local content from the previous generation and disseminate it to their students or apprentices, significantly contributing towards sustaining the handicraft industry in Malaysia. With the rise of mass industrial production, the master craftsman faces crucial challenges in sustaining the handicraft industry in Malaysia. Thus, this study highlights the significant role of master craftsmen in capturing and disseminating local content. The qualitative research approach has been adopted to explore the considerable roles of master craftsmen in capturing and disseminating local content in Malaysia. The master craftsman in weaving "mengkuang" leaves has been selected as an informant to know her experience becoming a master craftsman, particularly in weaving "mengkuang" leaves. The author processed the skill and knowledge of the master craftsman throughout the interview. It has been found that there are several significant pieces of knowledge captured by master craftsmen, including material and equipment used, the processes, traditional motive, and techniques that previous generations frequently used in producing product-based mengkuang. The ways master craftsmen capture and disseminate the local content of product-based mengkuang are further discussed in this paper.